INTERNATIONAL FINANCIAL REPORTING STANDARDS FOR SMALL AND MEDIUM ENTERPRISE (IFRS FOR SMES) AND THE STATEMENT OF ACCOUNTING STANDARDS (SAS): A COMPARATIVE STUDY - Chikwemma, Muotolu Peace; Ursula, Egungwu Ngozi; Sunday, Anichebe Alphonsus (International Journal of Finance and Accounting, 2016)
Purpose: Micro, small and medium-sized enterprises (SME) are the engines that propel the world economy; they are essential sources of jobs, they create entrepreneurial spirit and innovation in the economy and are thus crucial for fostering competitiveness and creativity. The objective of this study therefore, is to ascertain the need for International Financial Reporting Standard for Small and Medium Enterprises (IFRS for SMEs) instead of Statement of Accounting Standards (SAS), to ascertain the extent to which IFRS aids managements in attaining goals and objectives as well as improving its market share and to ascertain the challenges for Non-compliance (causes and penalties) with international financial reporting standard for Small and Medium Enterprises. Methodology: Analysis of variance (ANOVA) was used to test hypothesis. Results: The findings were; a major factor why IFRS is adopted by Nigeria is because other countries have adopted it, the size of entities to participate in IFRS for SMES varies, adopting a globally accepted financial reporting is relevant to small firms as they operate in a globalized world. Policy recommendation: This study recommends that the IASB should ensure full implementation/compliance of IFRS for SME by companies that fall under that category, the cost of acquiring IFRS education should also be subsidized for small firms by major accounting regulatory bodies in Nigeria.